REKAMAN POLA NADI PENDERITA NEFROPATI DIABETES TIPE 2 PADA AREA CUN ARTERI RADIALIS - Erni Yudaningtyas (Universitas Muhammadiyah Purwokerto, 2011)
Type 2 Diabetic Nephropathy disease is chronic kidney disease (CKD) caused by type 2 diabetes. One method to determine the existence of the disease in Traditional Chinese Medicine (TCM) is by palpation of the pulse at radial artery area. Pulse patterns were recorded non-invasively in normal subjects who are people with type 2 diabetes who have not experienced impaired kidney function and type 2 Diabetic Nephropathy pathological subjects with normal heart function. Systolic time showed that there were no significant differences between normal subjects and type 2 Diabetic Nephropathy pathological stage 1 to 3b, which is about 0.16 seconds. The longer systolic time were shown on pathological subjects stage 4 and 5, which is in this condition Diabetes Nephropathy disease can affect heart function. Keywords: Pulse pattern record, radial artery cun area, normal heart function, systolic time